The cross-talk of lung and heart complications in COVID-19: Endothelial cells dysfunction, thrombosis, and treatment - Liu, Langjiao; Jing, Haijiao; Wu, Xiaoming; Xiang, Mengqi; Novakovic, Valerie A.; Wang, Shuye; Shi, Jialan (Frontiers in Cardiovascular Medicine, 2022)
The pandemic respiratory illness SARS-CoV-2 has increasingly been shown to be a systemic disease that can also have profound impacts on the cardiovascular system. Although associated cardiopulmonary sequelae can persist after infection, the link between viral infection and these complications remains unclear. There is now a recognized link between endothelial cell dysfunction and thrombosis. Its role in stimulating platelet activation and thrombotic inflammation has been widely reported. However, the procoagulant role of microparticles (MPs) in COVID-19 seems to have been neglected. As membrane vesicles released after cell injury or apoptosis, MPs exert procoagulant activity mainly by exposing phosphatidylserine (PS) on their lipid membranes. It can provide a catalytic surface for the assembly of the prothrombinase complex. Therefore, inhibiting PS externalization is a potential therapeutic strategy. In this paper, we describe the pathophysiological mechanism by which SARS-CoV-2 induces lung and heart complications through injury of endothelial cells, emphasizing the procoagulant effect of MPs and PS, and demonstrate the importance of early antithrombotic therapy. In addition, we will detail the mechanisms underlying hypoxia, another serious pulmonary complication related to SARS-CoV-2-induced endothelial cells injury and discuss the use of oxygen therapy. In the case of SARS-CoV-2 infection, virus invades endothelial cells through direct infection, hypoxia, imbalance of the RAAS, and cytokine storm. These factors cause endothelial cells to release MPs, form MPs storm, and eventually lead to thrombosis. This, in turn, accelerates hypoxia and cytokine storms, forming a positive feedback loop. Given the important role of thrombosis in the disease, early antithrombotic therapy is an important tool for COVID-19. It may maintain normal blood circulation, accelerating the clearance of viruses, waning the formation of MPs storm, and avoiding disease progression.